Point of Sale (POS) Application Tire at the Diva Cirebon Store Based on Website - Ayumida, Surtika; Ratnawati, Ratnawati; Hakim, Lukmanul; Ichsan, Nurul (International Journal of Computer and Information System (IJCIS), 2025)
As technology develops, everyone wants easy things, one of which is the ease of shopping for tires and processing sales data. Manual data recording has several weaknesses, including the potential for errors in writing and reading, and is also prone to loss or damage. From the problems mentioned above, the ongoing management system that is carried out manually, makes sales data management not effective and efficient enough, so a more effective system is needed because it can be accessed quickly and easily, namely by developing a website-based Tire Point of Sale (POS) application at Toko Diva Cirebon. The purpose of making this Tire Point of Sale (POS) application is to help integrate data properly and enable easy and accurate data processing. The development of this system uses the waterfall system design method, which can assist in making the system by following a sequential process. This method is carried out starting from the requirements analysis stage, system and software design, implementation, system testing, and maintenance. Design tools use UML (Unified Modeling Language) to create use case diagrams, activity diagrams, and class diagrams. The results obtained are web-based Point of Sales (POS) applications that can facilitate recording, managing and storing data on goods and transactions carried out. This application helps minimize errors that may occur in transaction calculations and makes it easier to search for data.